2010 IEEE International Conference on Communications 2010
DOI: 10.1109/icc.2010.5502026
|View full text |Cite
|
Sign up to set email alerts
|

Power Allocation for Quasi-Orthogonal Space-Time Block Codes with 1 or 2 Bits Feedback

Abstract: In this paper, a closed-loop wireless communication system employing Quasi-Orthogonal Space-Time Block Codes (QOSTBCs) is presented, where the total available power can be suitably allocated to the four transmit antennas, considering a very low-complexity decoding scheme at the receiver side. After deriving a particular optimization problem concerning the optimal choice of the power weights, we prove that the best strategy in terms of error probability is to switch-off three out of the four transmit antennas u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…For the slow-fading channels, a single feedback bit scheme is proposed by employing the differential coding to exploit the smooth variation of the channel coefficients [10]. Similar research work has also been found on the quasi-orthogonal STBC [11][12][13]. Additionally, many researches have come into being focussing on the closedloop design by combining STBC with pre-coding [14,15], beamforming [16] or transmit antenna selection [17,18], and so on.…”
Section: Introductionmentioning
confidence: 88%
“…For the slow-fading channels, a single feedback bit scheme is proposed by employing the differential coding to exploit the smooth variation of the channel coefficients [10]. Similar research work has also been found on the quasi-orthogonal STBC [11][12][13]. Additionally, many researches have come into being focussing on the closedloop design by combining STBC with pre-coding [14,15], beamforming [16] or transmit antenna selection [17,18], and so on.…”
Section: Introductionmentioning
confidence: 88%
“…Rayleigh fading channels. It has been further shown in [14] that TAS/MRC outperforms all quasi-OSTBC schemes for i.i.d. Rayleigh fading channel.…”
Section: Introductionmentioning
confidence: 89%
“…Henceforth, we will use the notation z = 1/P t g(1 − r √ ) . The integral in (14) can be evaluated by linearising the product of incomplete gamma functions using the method given in [16]. Using the same method the linearised product is calculated in Appendix 1.…”
Section: Mimo System Employing Tas/mrc With Bpsk Modulationmentioning
confidence: 99%
“…Quantized feedback is a promising method to achieve notable performance gain in MIMO system by transmitting a few bits feedback about CSI from receiver to transmitter; so turns out to be practically suitable. In literature, it is shown that error performance of OSTBC and Quasi-OSTBC (QOSTBC) [10] can be improved by using quantized feedback of CSI at the transmitter [9], [11]- [14]. These works focused on design of diagonal weighting precoder for OSTBC and QOSTBC.…”
Section: Introductionmentioning
confidence: 98%